Assessing the Feasibility of Rural MSMEs in the Context of Industrial Growth in Nganjuk Regency - M. Aldi Ainul Rohim (Prodi Ekonomi Syariah Universitas Pangeran Diponegoro Nganjuk, 2025)
This study aims to analyze the business feasibility of rural Micro, Small, and Medium Enterprises (MSMEs) in Nganjuk Regency amidst the pressure of increasingly rapid industrial growth. The growth of the industrial sector provides economic opportunities, but also poses challenges for rural MSMEs, such as business competition, limited capital, and changes in market patterns. This study uses a qualitative method with a case study approach to several rural MSMEs in Nganjuk Regency. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis was carried out descriptively and analytically by assessing aspects of business feasibility including market, technical, management, and financial aspects in a non-numerical manner. The results of the study indicate that rural MSMEs in Nganjuk Regency are generally still feasible to operate, but require strengthening marketing strategies, increasing human resource capacity, and government policy support to be able to survive and compete with large-scale industries.